Noise exposure and auditory effects on preschool personnel - Fredrik Sjödin; Anders Kjellberg; Anders Knutsson; Ulf Landström; Lennart Lindberg (Noise and Health, 2012)
Hearing impairments and tinnitus are being reported in an increasing extent from employees in the preschool. The investigation included 101 employees at 17 preschools in Umeå county, Sweden. Individual noise recordings and stationary recordings in dining rooms and play halls were conducted at two departments per preschool. The effects of noise exposures were carried out through audiometric screenings and by use of questionnaires. The average individual noise exposure was close to 71 dB(A), with individual differences but small differences between the preschools. The noise levels in the dining room and playing halls were about 64 dB(A), with small differences between the investigated types of rooms and preschools. The hearing loss of the employees was significantly higher for the frequencies tested when compared with an unexposed control group in Sweden. Symptoms of tinnitus were reported among about 31% of the employees. Annoyance was rated as somewhat to very annoying. The voices of the children were the most annoying noise source. The dB(A) level and fluctuation of the noise exposure were significantly correlated to the number of children per department. The preschool sound environment is complex and our findings indicate that the sound environment is hazardous regarding auditory disorders. The fluctuation of the noise is of special interest for further research.